Design and custom fabrication of specialized orthoses for the upper-limb stabilization in childhood dyskinesia. Issue 6 (24th December 2022) - Garavaglia, Lorenzo; Pagliano, Emanuela; LoMauro, Antonella; Pittaccio, Simone
Abstract : Background: Childhood dyskinesia (CD) is a complex movement disorder with components of dystonic and hyperkinetic nature, characterized by involuntary, sometimes stereotypical postures and gestures that are often impossible to control and hinder the execution of willful motion. The standard orthoses for the treatment of neurological diseases, including CD, are generally poorly differentiated for functional characteristics. The application of similar devices for movement disorders is far less generalized because of the very different symptoms, including the incapacity to control rather than initiate movement. Objectives: This article aims to describe an innovative method to fabricate personalized orthoses for the elbow-wrist joints in CD, taking into account anatomical and functional diversities. It also proposes functional elements to implement the required dynamic postural control. Methods: Wearable custom-made upper-limb orthoses have been fabricated and preliminarily tested on five patients with CD. Optoelectronic stereophotogrammetry was used as an innovative tool for all-in-one–frame acquisition of limb geometry. A new process for the functional personalization of the orthoses has been developed using shape memory alloys. Conclusions: The innovative method presented, encompassing data acquisition, virtual design, fabrication, and assembling, overcomes the problems due to the involuntary movements of the patients, which cannot be avoided during the fitting operations, providing comfortable and useful orthoses with minimal nuisance for the patients. Initial tests show that the orthoses were well tolerated by all the subjects; the promising comments of caregivers, together with improvements, were observed by the clinicians using specific clinical scales.